2015
DOI: 10.1515/oere-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of allergic response using dynamic thermography

Abstract: Skin dynamic termography supplemented by a mathematical model is presented as an objective and sensitive indicator of the skin prick test result. Termographic measurements were performed simultaneously with routine skin prick tests. The IR images were acquired every 70 s up to 910 s after skin prick. In the model histamine is treated as the principal mediator of the allergic reaction. Histamine produces vasolidation and the engorged vessels are responsible for an increase in skin temperature. The model paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The inter-subject variability of the parameter can be considered as a confirmation that the immediate allergic response is a highly individual-dependent process, but its value can reflect the skin reactivity. Previous studies have confirmed that histamine migration rate is also parameter responsible for the maximal radius of the heated region (correlation coefficient = 0.85) [12,13]. A comparison of the histamine migration rate with age of patients seems to be interesting (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The inter-subject variability of the parameter can be considered as a confirmation that the immediate allergic response is a highly individual-dependent process, but its value can reflect the skin reactivity. Previous studies have confirmed that histamine migration rate is also parameter responsible for the maximal radius of the heated region (correlation coefficient = 0.85) [12,13]. A comparison of the histamine migration rate with age of patients seems to be interesting (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…The above rigorous analysis is not still satisfying because it does not allow to full explanation of about 10 % misinterpreted cases by SPT method. At this point very useful was the model analysis of thermograms which provides opportunity to determine the migration rate of the basic mediator of allergic reactionhistamine (v) [12,13]. Temporal acquisition of control histamine response allows estimating the migration rate of histamine (v) in the skin (average v = 0.013 ± 0.010 mm/ s, range: (0.007-0.041) mm/s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest skin reaction observed after the Prick test is to the positive control. Its size varies between 10 and 30 mm [6]. The diameter of the holes in the template is 20 mm, which may not, in some cases, cover the full size of the reaction to a histamine solution.…”
Section: Thermal Imaging Analysis Of Allergic Skin Reactions In Prick...mentioning
confidence: 99%
“…For this reason, it is necessary to initially capture the skin areas and reposition the arm (Figure 3). Most studies do not analyze the initial skin temperature, although it is the starting point for the temperature change [6][7][8]. There were no statistically significant differences in skin temperatures prior to the test when subcutaneous main blood vessels were avoided [9].…”
Section: Analysis Of the Temperature Of The Skin Areas Before Perform...mentioning
confidence: 99%